Deaths from primary brain cancers, lymphatic and haematopoietic cancers in agricultural workers in the Republic of Ireland. Issue 4 (August 1994) - Dean, G
Abstract : STUDY OBJECTIVE–To ascertain if agricultural workers in the Republic of Ireland had a higher than expected mortality from brain and haematopoietic cancers than occurred in the general population. DESIGN–The Central Statistics Office of Ireland provided computer analysis of all deaths coded as cancer of the brain, ICD 191, and of lymphatic and haematopoietic cancers, ICD codes 200-208, by socioeconomic, sex, and age groups, from 1971 to 1987. The deaths were then analysed by socioeconomic group and compared with the expected number of deaths in the general population. SETTING–A cluster of four deaths from primary brain cancer, three from leukaemia, and one from Hodgkin's disease, occurred in the research and technical staff of the former Agricultural Institute of the Republic of Ireland in men under the age of 65. This raised the question, were farmers more likely to get these forms of cancer due to exposure to herbicides or fertilisers? SUBJECTS–All deaths in the Republic of Ireland from 1971 to 1987 by socioeconomic group. MAIN RESULTS–Although deaths reported as due to primary brain cancers had increased in all socioeconomic groups in the two time periods studied, there was no greater increase in farmers and a smaller increase in other agricultural workers and fishermen. Deaths from Hodgkin's disease and multiple myeloma, and to a smaller extent from leukaemia, had also increased. The increase in reported mortality of these haematopoietic cancers in farmers was no greater and in other agricultural workers it was less than in the general population. CONCLUSION–There was no evidence that farmers had any greater increase in mortality from these cancers than the general population. The cluster of brain and haematopoietic cancers in research and technical staff at the Agricultural Institute of the Republic of Ireland does not reflect a high risk of these cancers among the general farming population, but strongly supports the need for a compilation of a register of causes of death of laboratory workers in a number of countries.